For this case we have the following equation:
[tex]-12.7 = y-3.4
[/tex]
From here, we must clear the value of y.
For this, we follow the following steps:
1) we add 3.4 on both sides of the equation:
[tex]-12.7 + 3.4 = y-3.4 + 3.4
[/tex]
2) We rewrite the right side of the equation:
[tex]-12.7 + 3.4 = y + 0
-12.7 + 3.4 = y[/tex]
3) We do the algebraic sum of the left side of the equation:
[tex]-12.7 + 3.4 = y
-9.3 = y[/tex]
Therefore, the solution of the equation is:
[tex]y = -9.3
[/tex]
Answer:
y = -9.3